2006
DOI: 10.1038/sj.cgt.7700997
|View full text |Cite
|
Sign up to set email alerts
|

Persistent mismatch repair deficiency following targeted correction of hMLH1

Abstract: The use of gene therapy to correct mutated or lost gene function for the treatment of human cancers has been an active, yet problematic area of biomedical research. Many technical difficulties, including efficient tissue-specific delivery, integration site specificity and general toxicity, are being addressed. Little is known, however, about the genetic and phenotypic stability that accompanies a successful gene-specific targeting event in a cancer cell. This question was addressed following the creation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To determine whether our observations were generally applicable to models of dMMR, we assessed the effect of cytarabine in other isogenic MLH1 and MSH2-deficient cell line pairs. We used the CRC cell lines, BVEC F7bro (MLH1-deficient) and BVEC E2 (MLH1-proficient) (Weiss et al , 2007), as well as LoVo (MSH2-deficient) and LoVo+Chr2 (MSH2 proficient) (Watanabe et al , 2000). We found that cytarabine was selective for MMR-deficient cell lines in both systems (Figures 2A and B), suggesting that this phenotype was applicable to multiple models.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether our observations were generally applicable to models of dMMR, we assessed the effect of cytarabine in other isogenic MLH1 and MSH2-deficient cell line pairs. We used the CRC cell lines, BVEC F7bro (MLH1-deficient) and BVEC E2 (MLH1-proficient) (Weiss et al , 2007), as well as LoVo (MSH2-deficient) and LoVo+Chr2 (MSH2 proficient) (Watanabe et al , 2000). We found that cytarabine was selective for MMR-deficient cell lines in both systems (Figures 2A and B), suggesting that this phenotype was applicable to multiple models.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have shown recently the discovery of genetic heterogeneity between single-cell clones after targeted knock-in of the hMLH1 gene in the MIN Table 2. Details of the 16 human cancer cell lines harboring K-ras mutations categorized by K-ras expression and allelic status cancer cell line HCT 116 (50). This property of MIN may also explain the differing degrees of tumorigenicity seen in studies using the same MIN DLD-1 colon cancer K-ras knockout clones (20,47).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a high-throughput synthetic lethal screen (48 h) to identify compounds that could selectively kill HCT116 MLH1 (–/–)-deficient cells but not its proficient counterpart, HCT116 MLH1 (+/–). The parental HCT116 MLH1 (–) cells carry a hemizygous point mutation (C755A) in exon 9 of the MLH1 gene, 24 resulting in a premature stop codon and loss of protein function, whereas the isogenic counterpart has a heterozygous knock-in of wild-type MLH1 allele (+/–) 25 ( Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…To further support our observation, we generated an MLH1 isogenic line from HT29 cells using the CRISPR-Cas9 technique. Compared with the HCT116 isogenic, which is a knock-in of MLH1 25 , the HT29 isogenic contains a knockout of MLH1 . As shown in Figure 2c , loss of MLH1 protein was found in five out of nine MLH1 -edited HT29 lines, encoded as HT29(MLH1 -)1, HT29( MLH1 -)2a, HT29( MLH1 -)2b, HT29( MLH1 -)2c, and HT29( MLH1 -)3, respectively.…”
Section: Resultsmentioning
confidence: 99%